2010
DOI: 10.1590/s0100-67622010000100001
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento inicial de Eucalyptus tereticornis em plantios puro e consorciado com Mimosa caesalpiniifolia E Mimosa pilulifera, em Campos dos Goytacazes-RJ

Abstract: RESUMO -Este trabalho objetivou avaliar o crescimento inicial de

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…The use of buffer methods studied by PRADO et al (2020) to estimate soil potential acidity indicated that the overestimation or underestimation of soil potential acidity may incur a limestone dosage error during the management of soil fertility (liming). BALBINOT et al (2010), studying the intercropping between E. tereticornis, and Mimosa caesalpiniifolia and Mimosa pilulifera, observed a reduction in effective CEC, sum of bases, Mg, P, Ca content and base saturation (%) of the soil, while, at the same time, pH, N, Na, Al and H + +Al +3 values increased in all planting systems. These results corroborated the high exchangeable potential acidity obtained in this study at 34 years of age.…”
Section: Resultsmentioning
confidence: 93%
“…The use of buffer methods studied by PRADO et al (2020) to estimate soil potential acidity indicated that the overestimation or underestimation of soil potential acidity may incur a limestone dosage error during the management of soil fertility (liming). BALBINOT et al (2010), studying the intercropping between E. tereticornis, and Mimosa caesalpiniifolia and Mimosa pilulifera, observed a reduction in effective CEC, sum of bases, Mg, P, Ca content and base saturation (%) of the soil, while, at the same time, pH, N, Na, Al and H + +Al +3 values increased in all planting systems. These results corroborated the high exchangeable potential acidity obtained in this study at 34 years of age.…”
Section: Resultsmentioning
confidence: 93%
“…(Migacz et al, 2018). Various studies have been performed in order to evaluate the interference of environmental conditions in the growth, productivity, and sustainability of E. tereticornis production systems (Rao et al, 2002; Balbinot et al, 2010; Sreevani & Rao, 2014; Duan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%